STRATEGI INDUSTRI PERBANKAN DI SUMATERA BARAT: PEMILIHAN SEGMENTASI PASAR UNTUK MENCIPTAKAN PELAYANAN YANG MEMUASKAN - RONI ANDESPA (Universitas Islam Negeri Imam Bonjol Padang, 2016)
This study examines the issue of consumer perception, consumer characteristics, responsiveness and reliability, and market segmentation. This study aims to: (1) Assess whether there are differences in the perception of consumers based on their background to the responsiveness and reliability. (2) Looking at the relationship between consumer characteristics with the responsiveness and reliability. (3) Determine the market segmentation which to be a market for the bank. The sample was 500 people (250 consumers from conventional banks and Islamic banks 250 consumers). The sampling technique is non-probability sampling. Analyzed using Pearson Cross Tabulation and Chi-Square test. In conventional banks found a significant relationship between variable responsiveness to consumer education and type of work. In Islamic bank found a significant correlation between reliability with gender. Banks operating in West Sumatra have to perform market segmentation based on education, type of work and gender of consumers.